Cloning and sequencing of Schizosaccharomyces pombe DNA topoisomerase I gene, and effect of gene disruption. - Uemura, T (1987)
We cloned the structural gene topl+ for Schizosaccharomyces pombe DNA topoisomerase I (topo I) by hybridization. An eight-fold increase of topo I relaxing activity was obtained in S. pombe cells transformed with multicopy plasmid with topl+ insert. Nucleotide sequence determination showed a hypothetical coding frame interrupted by two short introns, encoding a 812 residue polypeptide (M.W. 94,000), 43 residues longer than and 47% homologous to Saccharomyces cerevisiae topo I. We show that the topl (null) strain made by gene disruption is viable, although its generation time is 20% longer than that of wild type. The topl locus is mapped in the long arm of chromosome II, using the Leu+ marker integrated with the cloned topl+ sequence. We constructed a double mutant topl (null) top2 (ts) and found its defective phenotype similar to that of previously obtained topl (heat sensitive) top2 (ts). The other double mutant topl (null) top2 (cs), however, was lethal. Our results suggest that topl+ gene of S. pombe is dispensable only if topo II activity is abundant.